PENGARUH MENGKONSUMSI PISANG AMBON TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DI KLINIK SUWARTI KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2020 - Tampubolon, Nanda Pratama; Hayati, Erlina; Singarimbun, Elisabeth; Suriani, Suriani (JURNAL ILMIAH DHDT - KEBIDANAN, 2021)
Anemia is a condition in which the number and size of red blood cells or hemoglobin concentration is below normal limits, as a result it can interfere with the blood's capacity to carry oxygen around the body. Anemia is an indicator for poor nutrition and poor health. There are two efforts that can be made in the prevention and control of anemia, namely p Anemia is a condition in which the number and size of red blood cells or hemoglobin concentration is below normal limits, as a result it can interfere with the blood's capacity to carry oxygen around the body. Anemia is an indicator for poor nutrition and poor health. There are two efforts that can be made in the prevention and control of anemia, namely pharmacology by consuming Fe tablets. In addition to pharmacological therapy, non-pharmacological therapy can also be given. Ambon banana is one of the non-pharmacological therapies that is consumed as a staple food in the tropics. The purpose of this study was to determine the effect of consuming Ambon banana on increasing hemoglobin levels in pregnant women at the Suarti clinic, Old Deli District. This type of research uses a quasi-experimental method (Quasi-Experimental) with a One Group pretest - posttest design. The population in this study were all pregnant women who performed ANC examinations with anemia at the Suwarti clinic and the sampling technique used was total sampling with a total of 14 pregnant women. Engineering analysis using the Dependent T-test and the results obtained by using the Dependent T-test is p value <0.05, namely 0.000. So it is proven that there is a significant effect between the score of increasing hemoglobin levels (HB) before consuming Ambon banana and after consuming Ambon banana. harmacology by consuming Fe tablets. In addition to pharmacological therapy, non-pharmacological therapy can also be given. Ambon banana is one of the non-pharmacological therapies that is consumed as a staple food in the tropics. The purpose of this study was to determine the effect of consuming Ambon banana on increasing hemoglobin levels in pregnant women at the Suarti clinic, Old Deli District. This type of research uses a quasi-experimental method (Quasi-Experimental) with a One Group pretest - posttest design. The population in this study were all pregnant women who performed ANC examinations with anemia at the Suwarti clinic and the sampling technique used was total sampling with a total of 14 pregnant women. Engineering analysis using the Dependent T-test and the results obtained by using the Dependent T-test is p value <0.05, namely 0.000. So it is proven that there is a significant effect between the score of increasing hemoglobin levels (HB) before consuming Ambon banana and after consuming Ambon banana.